Canonical and noncanonical regulatory roles for JAK2 in the pathogenesis of rheumatoid arthritis‐associated interstitial lung disease and idiopathic pulmonary fibrosis. Issue 6 (6th May 2022) - Wang, Shaohua; Liu, Mengfei; Li, Xiujuan; Zhang, Jie; Wang, Faping; Zhang, Chujie; Roden, Anja; Ryu, Jay H.; Warrington, Kenneth J.; Sun, Jie; Matteson, Eric L.; Tschumperlin, Daniel J.; et al.
Abstract: Idiopathic pulmonary fibrosis (IPF) and rheumatoid arthritis‐associated interstitial lung disease (RA‐ILD) are two fibrotic interstitial lung diseases that share the usual interstitial pneumonia (UIP) injury pattern. Here, we report that RNA sequencing of lung biopsies from patients with RA‐ILD and IPF revealed shared and distinct disease‐causing pathways. Analysis of transcriptomic data identified a JAK2 related JAK/STAT signaling pathway gene signature that distinguishes RA‐UIP from idiopathic UIP. This was further confirmed by immunohistostaining, which identified JAK2 phosphorylation with two distinct forms of activation: a cytoplasmic form of JAK2 activation in most IPF cases (13/20) and a nuclear form of p‐JAK2 in RA‐UIP (5/5) and a minority of IPF (6/20) cases. Further immunohistostaining identified STAT5A&B as the downstream transcriptional activator for JAK2‐mediated canonical signal transduction and phosphorylation of Tyr41 on histone H3 (H3Y41ph) as the downstream epigenetic regulation site for JAK2‐mediated noncanonical signal transduction. Gene Set Enrichment Analysis (GSEA) of the RNA‐Seq data further supported this shared pathogenic mechanism for the two diseases with the enrichment of STAT5A&B target gene sets as well as the JAK2 regulated H3Y41ph target gene set. This regulatory role of JAK2 in the pathogenesis of pulmonary fibrosis was further demonstrated by the attenuation of bleomycin‐induced murine pulmonary fibrosis using a JAK2‐selective pharmacological inhibitor CEP33779. In vitro studies with normal and IPF derived lung fibroblasts revealed a central role for JAK2 as an essential intermediary molecule in TGF‐β‐mediated myofibroblast trans‐differentiation, proliferation, and extracellular matrix protein production. These observations support a crucial role for JAK2 as an intermediary molecule in fibrotic lung disease development.